PENGARUH KESIAPAN MENJADI ORANG TUA DAN POLA ASUH PSIKOSOSIAL TERHADAP PERKEMBANGAN SOSIAL ANAK - Setyowati, Yuli Dwi; Krisnatuti, Diah; Hastuti, Dwi (Jurnal Ilmu Keluarga dan Konsumen, 2017)
The purpose of this study was to analyze the effect of parenthood readiness and parenting psychosocial to social development in 2-3 years old. This study used cross sectional dan retrospective design in the Village Besar, Labuhan Subdistrict, and Village Medan Area, Kota Matsum Subdistrict, Medan City. One hundred families selected by purposive sampling child and mother as respondents. Data were analyzed using Partial Least Square (PLS). The questionnaire of Parenthood Readiness used for assessing readiness to become parenthood, HOME Inventory to assessing parenting psychosocial and Vineland Social Maturity used for Social Development in 2-3 years old. Parenthood readiness was categorized by the index average of 72,1±11,07. Nearly two-thirds of families (62,0%) have psychosocial parenting categorized amateurish with an index average 56,2±16,3. Mostly of children have social development categorized less independent (62,0%) with an index average 56,5±14,9. The higher age of maternal and paternal, more ready to become parents and good in psychosocial parenting. These will increase opportunities for social development for children to become independent.